Effect of Using Rice Husk Ash on the Growth of Chili (Capsicum annuum L.) - Okta Septi Hariani (Contributions of Central Research Institute for Agriculture, 2023)
Big chili (Capsicum annuum L.) is one of the vegetables that the request is high enough. One of the way to increase the production and quality of chili crops is by using a fertilizer that aims in increasing the supplay of nutrients needed by plants, that is by using the rice husk ash of waste factory beside giving the benefit of many biomass it also easy to be gotten. The objectives of this study were to know the influence of the use of rice husk ash for the plant of big chili plant with diffrent quality, and to know which one of the best for the plant to produce big chili with high quality. This research was conducted at MIPA Laboratory of Tarbiyah Faculty, IAIN Raden Fatah Palembang. The research used completely randomized design with 4 treatments and 3 replications, so we got 12 units of the experiment. The treatment were P0=0 gram/polybag, P1=24 gram/polybag, P2=48 gram/polybag, and P3=72 gram/polybag. The result of this research showed that giving 24 gram of rice husk ash got the average plant height 22,67 cm, the total stalks were 13,33, the age when the first flowering day was 50 days, and the total chili were 3,33. The treatment of 48 gram got the average plant height 27,17 cm, the total stalks were 21,33, the age when the first flowering day were 55,67 days and the total chili were 8,67. The treatment of 72 gram got the average plant height 33,33 cm, the total stalks were 35,33, the age when the first flowering day were 44,33 days and the total chili were 22. From the result of the research it can be conclude that the level of 72 gram/polybag give the best result for the growing of chili plant compared with another treatments.